Thermoelectric Method of Plastic Deformation Detection; Materials Science Forum; Vol. 938 : Materials and Technologies in Mechanical Engineering - Soldatov A. I. Aleksey Ivanovich; Soldatov A. A. Andrey Alekseevich; Sorokin P. V. Pavel Vladimirovich; Abouellail A. A. S. A. R. Ahmed Ali Sabri Ahmed Refaat; Kostina M. A. Maria Alekseevna (2018, 2018)
Title screen